Hubungan Identiti Korporat Dan Reputasi Korporat UNIMAS - Siti Haslina, Hussin; Awang Ideris, Awg Daud; Khadijah, Mohamad Tuah; Jamilah, bt. Maliki (Universiti Malaysia Sarawak, 2014)
Working Paper No. 70, June 2014